2007
DOI: 10.1016/j.devcel.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Rab25 Associates with α5β1 Integrin to Promote Invasive Migration in 3D Microenvironments

Abstract: Here, we report a direct interaction between the beta1 integrin cytoplasmic tail and Rab25, a GTPase that has been linked to tumor aggressiveness and metastasis. Rab25 promotes a mode of migration on 3D matrices that is characterized by the extension of long pseudopodia, and the association of the GTPase with alpha5beta1 promotes localization of vesicles that deliver integrin to the plasma membrane at pseudopodial tips as well as the retention of a pool of cycling alpha5beta1 at the cell front. Furthermore, Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
367
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(388 citation statements)
references
References 41 publications
(49 reference statements)
16
367
4
1
Order By: Relevance
“…Consistent with this observation, in vivo, upregulation of Ptc1 expression in response to the activation of the classical Shh signaling pathway is only observed from 18 to 24 hpe, concomitant with the effect of Shh misexpression on neural proliferation and dorsoventral patterning. A possibility is that Shh activity affects intracellular trafficking of ␤1 integrins via Rab-GTPases known to associate directly with them to favor cell migration (Caswell et al, 2007). However, blocking HH signaling pathway in zebrafish by cyclopamine induces cells to inappropriately exit the spinal cord, a phenotype reminiscent of our loss-of-function experiments (Ungos et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with this observation, in vivo, upregulation of Ptc1 expression in response to the activation of the classical Shh signaling pathway is only observed from 18 to 24 hpe, concomitant with the effect of Shh misexpression on neural proliferation and dorsoventral patterning. A possibility is that Shh activity affects intracellular trafficking of ␤1 integrins via Rab-GTPases known to associate directly with them to favor cell migration (Caswell et al, 2007). However, blocking HH signaling pathway in zebrafish by cyclopamine induces cells to inappropriately exit the spinal cord, a phenotype reminiscent of our loss-of-function experiments (Ungos et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…These results indicated that Rab25 is an oncogene-like protein that promotes tumour growth in ovarian and breast cancer models 4,5 , but acts as a tumour growth suppressor in intestinal epithelial cells, which raises the question of why the same Rab protein functions differently in different cancers. Such discrepancy was also found for hRAB37 in lung cancer and renal cell carcinoma where KD of hRAB37 reduced cell growth of renal cell carcinoma cell lines 29 .…”
Section: Article Nature Communications | Doi: 101038/ncomms5804mentioning
confidence: 99%
“…It should also be noted that the findings of Pellinen et al [2006] and Caswell et al [2007] have fundamental differences. In the first place, the two Rabs appear to interact with different integrin subunits.…”
Section: Rabs Integrin Traffic and Cancer Cell Adhesion/migrationmentioning
confidence: 90%
“…Silencing of Rab25 resulted in exactly the opposite phenotypes. Caswell et al [2007] found that the b1 subunit of integrin and a5b1 heterodimers (but not avb3) could associate with over-expressed epitope-tagged Rab25 in A2780 ovarian cancer cells. This interaction was confirmed by reciprocal pull-down analysis, is GTP-dependent and is specific for Rab25, as neither Rab11A nor Rab11B interacted in the same manner.…”
Section: Rabs Integrin Traffic and Cancer Cell Adhesion/migrationmentioning
confidence: 92%
See 1 more Smart Citation